1997
DOI: 10.1074/jbc.272.49.30899
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an African Swine Fever Virus 20-kDa DNA Polymerase Involved in DNA Repair

Abstract: African swine fever virus (ASFV) encodes a novel DNA polymerase, constituted of only 174 amino acids, belonging to the polymerase (pol) X family of DNA polymerases. Biochemical analyses of the purified enzyme indicate that ASFV pol X is a monomeric DNA-directed DNA polymerase, highly distributive, lacking a proofreading 3-5-exonuclease, and with a poor discrimination against dideoxynucleotides. A multiple alignment of family X DNA polymerases, together with the extrapolation to the crystal structure of mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
119
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 75 publications
(74 reference statements)
3
119
0
Order By: Relevance
“…Homologs of all BER proteins except the oxidative DNA glycosylases have been identified and characterized in African Swine Fever Virus (AFSV) [46,47]. The giant Mimivirus also carries all BER proteins including a recently characterized DNA ligase [48] and the two oxidative DNA glycosylases, MvNei1 and MvNei2 described in this paper.…”
Section: Ber In Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Homologs of all BER proteins except the oxidative DNA glycosylases have been identified and characterized in African Swine Fever Virus (AFSV) [46,47]. The giant Mimivirus also carries all BER proteins including a recently characterized DNA ligase [48] and the two oxidative DNA glycosylases, MvNei1 and MvNei2 described in this paper.…”
Section: Ber In Virusesmentioning
confidence: 99%
“…3) suggesting a role in the viral BER pathway. Homologs of human Polβ have been identified in both ASFV and Mimivirus [21,46]. The ASFV polX missing the N-terminal 8-kDa domain is unlikely to exhibit dRP lyase activity whereas the mimiviral PolX carries the putative dRP lyase domain.…”
Section: Ber In Virusesmentioning
confidence: 99%
“…Though data were not actually provided, Blanco and coworkers have indicated that Pol X is not expressed until the later stages of ASFV infection (52), whereas the ASFV replicative polymerase is expressed at both early and late stages of infection (59,60). It would therefore appear that if Pol X is indeed involved in TLS, it shows up at the last minute to rescue severely hindered replisomes.…”
Section: Utilization Of Damaged Substrates By Pol X and The Biologicamentioning
confidence: 99%
“…Despite its relatiVely efficient usage of 8-oxo-dGTP, the minimal number of incorporation events that Pol X is expected to catalyze per genome [since it is a repair or perhaps a TLS, not a replicative, polymerase (9,51,52)] suggests that 8-oxo-G is probably not incorporated very frequently. Once incorporated into a single-nucleotide gap, persistence of 8-oxo-G in the genome would be dependent upon the relative efficiencies of the competing reactions catalyzed by ASFV APE (removal of 8-oxo-G via its 3′ f 5′ exonuclease editing activity) 8 and ASFV DNA ligase (sealing the 8-oxo-G-containing nick to give a stable, contiguous duplex).…”
Section: Utilization Of Damaged Substrates By Pol X and The Biologicamentioning
confidence: 99%
“…Additionally, the inhibition of the polymerization activity in the presence of ddNTPs is in agreement with a poor discrimination of the 3´-OH group of the incoming nucleotide, this fact being a general catalytic feature of this family of DNA polymerases 12,36,38 .…”
Section: Structural Features Of Polβ-like Core Of Bacterial/archaeal mentioning
confidence: 79%